2001
DOI: 10.1046/j.1365-2826.2001.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Projections from the A1 Field to the Preoptic Area in the Brain of the Ewe and Fos Responses to Oestrogen in the A1 Cells

Abstract: Previous studies have shown that there is a population of noradrenergic cells in the caudal A1 field of the brainstem of the ewe that contain oestrogen receptors and project to the preoptic area, where gonadotrophin releasing hormone (GnRH) neurones are located. There are some discrepancies in the literature regarding the extent of this projection and the location of the cells in the A1 region. The issue has been a focus of attention because the positive feedback response to oestrogen that causes the ovulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…TH-ir fibers have been observed in close association with GnRH neurons in the ewe [17], but this input most likely is noradrenergic. Retrograde tracing studies [11] have shown that numerous DBH-ir (presumably noradrenergic) neurons in the ventrolateral medulla of the brain stem (A1 cell group) project to the rostral preoptic area in the ewe. The present study indicates that a similar pathway exists in the ram, although the physiological significance of this pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TH-ir fibers have been observed in close association with GnRH neurons in the ewe [17], but this input most likely is noradrenergic. Retrograde tracing studies [11] have shown that numerous DBH-ir (presumably noradrenergic) neurons in the ventrolateral medulla of the brain stem (A1 cell group) project to the rostral preoptic area in the ewe. The present study indicates that a similar pathway exists in the ram, although the physiological significance of this pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the ewe, some orexin-containing neurons in the lateral hypothalamus provide direct input to GnRH neurons [10]. Noradrenergic neurons of the ventrolateral medulla in the caudal brain stem also project to the medial preoptic area in the ewe [11]. These neurons contain estrogen receptors [12] and thus may be involved in the feedback regulation of GnRH secretion by this steroid.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical and physiological studies in this species have implicated catecholaminergic, neuropeptide Y (NPY)ergic, ␥-aminobutyric acid (GABA)ergic and opioidergic systems, among others, as potential transducers of steroid feedback onto the GnRH system. Specifically, dopamine (DA) is suggested to mediate estrogen-negative feedback via an inhibitory influence on the GnRH system during AN (29 -32), whereas the role of norepinephrine may vary depending on the stage of the annual reproductive cycle (30,33,34). An inhibitory influence of GABA on the GnRH system is suggested and may be expressed during negative feedback in AN and during negative feedback throughout the estrous cycle (35,36).…”
Section: Y Early Cycles Of Fertility and Infertility In Sheep Andmentioning
confidence: 99%
“…Yet despite their possible presence, our findings would suggest that noradrenergic systems are not able to influence GnRH in a fashion that involves altering their numbers of inputs onto GnRH neurons. However, as for DA, a possible change in activation of these afferents by estradiol cannot be discounted and indeed may be an important mechanism for regulating GnRH, especially during the estrous cycle (34). A final possibility is that NE could modulate GnRH via corelease at terminals other than those expressing TH-ir.…”
Section: Seasonal Variation In Gnrh Inputsmentioning
confidence: 99%
“…In spontaneous ovulators, NE release (estimated by microdialysis or turnover rate) increases in the POA and median eminence before and during the preovulatory LH surge in rats, 258,259 sheep, [260][261][262] and monkeys. 263 These species differ in the source of this NE input; both the A2 264-266 and A6 267-269 NE groups appear to be important in rats, whereas the A1 270,271 and A6 263 NE groups have been implicated in sheep and monkeys, respectively. The relative importance of NE to the normal surge also varies among these species ( Figure 33.8), with α-adrenergic antagonists completely blocking the surge in rats, 27,259 but having no effect in primates.…”
Section: Neural Circuits Responsible For the Control Of The Gnrh Surgmentioning
confidence: 99%